DEVELOPMENT AND APPLICATION OF APPROPRIATE TECHNOLOGY TO RECYCLE WASTE PERFORMED - Ayu Arwati, I Gusti; Nina Saparina Yuliani, Euis; Endah Retno Wuryandari, Nur; Lutfiana, Diana (Dinasti International Journal of Management Science, 2021)
The program of development and application of appropriate technology to recycle waste is executed by SMEs Bank Sampah (Waste Bank) Bumi Hijau Cemerlang Desa Suradita Tanggerang. The team was established since 2015. The management of this waste bank foundation is always energetic and productive so as they are competent to collect 200 kg inorganic waste (plastic and paper) in one week. On the other side, they did recycling liquid fertilizer from organic waste by using the used composter. This action is performed by realizing the fact that household waste matter gets heaped and malignant towards environment. The are problems faced by the team. Providing learning assistance in the form of appropriate technology tools and how to use them. In order to ensure the successful of this program, evaluation is carried out in every step of the program’s development.